2010
DOI: 10.4028/www.scientific.net/amr.108-111.1043
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Techniques for Predicting Pyroshock Responses of Aerospace Structures

Abstract: Pyroshock responses of aerospace structures/systems are significantly important for design and valuation of space systems because it is a harsh environment for the systems, especially the electrical components. But the designers strongly rely on tests because, up to now, there have not been effective analytical and even numerical techniques for this problem. Fortunately, a number of researchers have been making efforts to build numerical techniques for structural responses prediction under this kind of special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In addition, finite element analysis has been used to simulate pyroshock in the lowfrequency regime such as the far field. However, the finite element models used were not accurate for numerical simulation of the high-frequency structural response [12,13]. Recently, research has involved simulation of pyroshock experimentally using laser shock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, finite element analysis has been used to simulate pyroshock in the lowfrequency regime such as the far field. However, the finite element models used were not accurate for numerical simulation of the high-frequency structural response [12,13]. Recently, research has involved simulation of pyroshock experimentally using laser shock.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations described above, we developed a hybrid method of modal analysis and laser shock scanning to simulate the pyroshock over the whole frequency regime. In the far field, with low-frequency components less than 3 kHz, because the finite element analysis verified the accurate simulation performance [12,13], the far-field pyroshock was simulated using the modal analysis. In the mid and near field, because the laser shock-based experimental simulation provided accurate simulation performance [14], the mid-and near-field pyroshock over 3 kHz was simulated using laser shock.…”
Section: Introductionmentioning
confidence: 99%
“…This high-acceleration, high frequency pyroshock can induce malfunction of electrical components of a launch vehicle or a satellite, resulting in a catastrophic mission failure [1]. Therefore prediction of the shock induced responses of structures is an essential work when pyro devices are employed [2]. For this practical purpose, an empirical method based on the measurement data of heritage programs used to be applied just to obtain an approximated level of shock that would be induced in structural parts of interest [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, recent research into Hydro-code-based pyroshock simulation has been reported as suitable for simulating highly dynamic phenomena such as pyroshock [13][14][15]. However, most of these numerical techniques required accurate knowledge of all parameters of the structure to obtain reliable simulation results, and computational time and cost limitations emerged when applied to complex structures [16,17].…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…In this section, pyroshock data in ref [16] was secured to verify and compare the performance of the developed algorithm ( Table 1). The pyroshock data were obtained by exploding the linear pyrotechnical device in the quasi-isotropic CFRP sandwich panel.…”
Section: Reconstruction Of Linear Explosive Induced Pyroshock In Cfrpmentioning
confidence: 99%